An analysis of eclectic theatre in Iran based on Ta’ziyeh / Farideh Alizadeh - Farideh, Alizadeh (2015)
This present study analyses a kind of eclectic theatre in Iran based on Ta’ziyeh. Ta’ziyeh is well known as a kind of ritual form in Iran which contains tradition, religion and myth. In the contemporary setting, many directors and playwrights have been influenced by the form and content of Ta’ziyeh and use it in their works. The purpose of studying here is to analyse plays which influenced by Ta’ziyeh. Eclectic theatre is a new theory in postmodern theatre studies, which can be manifested in connection with theatre activities of Iran. Specific theatrical forms have been developed in many geographical-cultural areas of the world which are indigenous to those areas. Ta’ziyeh is a kind of comprehensive indigenous form considered as being the national form of Iranian theatre which have pervasive influence in the Iranian works of drama and play. It originates from some famous mythologies and rites such as Mithraism, Sug-e-Siavush (The Lamentation of Siavush) and Yadegar-e-Zariran. Ta’ziyeh was developed in the Safavid period (1502–1736 CE) in Iran when the king of Iran allowed Ta’ziyeh groups to perform it at Muharram time. Originally the Ta’ziyeh depicts the Karbala events. Generally, the Ta’ziyeh plays can be divided according to subject matter and content into three basic categories. First, there are those plays that deal only with the events of the Karbala and the martyrdom of Imam Husain and his followers. Second, there are those that deal with other subjects taken from a variety of sources such as history. The third part deals with farcical plays, such as ‘feminine Ta’ziyeh’. Although, they seem to be separate, they are still connected to the Karbala events through either a verbal or a staged digression1 (guriz2) that dramatizes the suffering and death of Imam Husain. The Ta’ziyeh has influenced many Iranian theatre directors in recent years. Most Iranian directors and playwrights, especially since the 1970s, still think and write in a western style. They have brought the ‘form’ and ‘content’ of Ta’ziyeh into their work and combined them with western influenced theatre styles to create a new genre of works. This new style is known as ‘eclectic theatre’ or ‘eclecticism’, which is a new style in postmodernism. For instance, the play A Lonely Person’s Story is taken from the Ta’ziyeh the Martyrdom of Imam Husain (Amini, 2004). Ashaghe (Story of Love) (Rahmanian, 2007) and Ghadamshad the Minstrel’s Martyrdom-Playing in Tehran (Rahmanian, 2006) were taken from ‘feminine Ta’ziyeh’. In this study, I will analyse these three mentioned plays, based on ‘eclectic theatre’, as clear examples of Ta’ziyeh-influenced theatre as eclectic theatre in Iran. To this purpose, I have made some classifications and criteria determined by watching performances, based on techniques and methods of Ta’ziyeh, and analysed those plays through eclecticism as an alternative form in postmodern theatre. This method has proved favourable for comparative studies on one part, while the Iranian theatrical forms have been more clear and researchable, on the other.